Prevalence of Metabolic Syndrome in Treatment Naïve Rheumatoid Arthritis and Correlation With Disease Parameters - Purneshwar Kumar PANDEY; Abhijit SWAMI; Tanuj Kumar BISWAS; Riturag THAKURIA (Archives of Rheumatology, 2017)
Objectives: This study aims to assess the prevalence of metabolic syndrome (MetS) in treatment naïve rheumatoid arthritis (RA) in an Indian population and correlate RA disease characteristics with presence of MetS. Patients and methods: The study included 84 RA patients (18 males, 66 females; mean age 44.8±12.5 years; range 18 to 72 years) diagnosed according to 2010 American College of Rheumatology-European League Against Rheumatism classification criteria who were treatment naïve or did not receive disease modifying antirheumatic drugs for more than six weeks and 120 age and sex-matched apparently healthy controls (35 males, 85 females; mean age 44.1±12.7 years; range 18 to 75 years). The frequency of MetS was assessed using National Cholesterol Education Program- Adult Treatment Panel III 2004 revised criteria. Patients were also assessed in terms of disease activity, using disease activity score 28 erythrocyte sedimentation rate. Logistic regression was used to identify predictors of MetS in RA. Results: Metabolic syndrome was found in 39.28% of RA group and 20% of control group according to National Cholesterol Education Program- Adult Treatment Panel III 2004 (p<0.005). MetS was most commonly detected in the 51 to 60 age group (65%). RA group was significantly more likely to have low high-density lipoprotein (63.09%), high triglyceride (53.57%), elevated blood pressure (41.66%) levels, and elevated waist circumference (38.09%). In RA group, disease activity score 28 (odds ratio: 6.51, confidence interval: 1.19-35.46 p=0.03), C-reactive protein (odds ratio: 1.13, confidence interval: 1.05-1.21 p<0.001), and duration of disease (odds ratio: 1.82, confidence interval: 1.04-3.18 p=0.03) remained independent predictors for presence of MetS in RA. Conclusion: The frequency of MetS was higher in RA group compared to control group. Higher systemic inflammatory marker, disease duration, and disease activity score 28 remained independent predictors associated with presence of MetS. These findings suggest that RA patients should be screened early for presence of MetS to check for and reduce risk of atherosclerotic vascular diseases.